Dinamika Mekanisme Kerja Obat dalam Kajian Farmakologi: Studi Pustaka dengan Pendekatan Kualitatif - Antonius Padua Ratu; Euis Pujasari Hardjadipura (PT Bukuloka Literasi Bangsa, 2025)
This study aims to analyze the dynamics of drug mechanisms in pharmacology through a qualitative approach based on literature review to gain a comprehensive understanding of its conceptual and implementational developments. The method used was qualitative research with a descriptive approach through literature studies, with data collection techniques in the form of literature searches, document analysis, and theoretical studies of scientific articles and relevant academic sources. Data analysis was carried out thematically through the stages of theme identification, data reduction, concept categorization, and inductive conclusion drawing to synthesize the findings systematically. The results of the study show that the mechanism of drug action is no longer understood reductionistically as a single interaction between a drug and a single biological target, but rather as a multidimensional process involving multiple molecular pathways, immune responses, regulatory validation, and the dynamics of communication and social context. These findings confirm a paradigm shift towards a systemic and interdisciplinary approach in modern pharmacology, including the integration of ethnopharmacology and health policy management. Overall, this study contributes to expanding the theoretical understanding of drug mechanisms of action and provides a conceptual basis for the development of more adaptive, evidence-based, and contextual pharmaceutical policies and practices. Keywords: drug mechanism of action, pharmacology, literature review, qualitative approach, health policy